2018
DOI: 10.1016/j.neuroimage.2017.10.049
|View full text |Cite
|
Sign up to set email alerts
|

Combining images and anatomical knowledge to improve automated vein segmentation in MRI

Abstract: The accuracy of automated vein segmentations derived from the composite vein image was overwhelmingly superior to segmentations derived from SWI or QSM alone.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 52 publications
3
23
0
Order By: Relevance
“…On average, intersubject variability decreased with increasing vessel diameter (Figure 3)where vessels with diameters >$2.5 mm tended to be most stable across subjects. This is in line with another study which examined cerebral veins in 10 subjects and reported high intersubject probabilities near the major veins, including in the superior sagittal sinus, dural sinuses, straight sinus, and internal cerebral veins(Ward et al, 2018). Notably, this relationship was also observed in arteries(Figure 3, R = [.46, .52], all p < .001).Moreover, to the best of our knowledge, no group-based probabilistic venous atlas with a relatively large number of healthy subjects (more than 10) exists in the literature(Nils Daniel Forkert et al, 2012), making ours the first publicly available.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…On average, intersubject variability decreased with increasing vessel diameter (Figure 3)where vessels with diameters >$2.5 mm tended to be most stable across subjects. This is in line with another study which examined cerebral veins in 10 subjects and reported high intersubject probabilities near the major veins, including in the superior sagittal sinus, dural sinuses, straight sinus, and internal cerebral veins(Ward et al, 2018). Notably, this relationship was also observed in arteries(Figure 3, R = [.46, .52], all p < .001).Moreover, to the best of our knowledge, no group-based probabilistic venous atlas with a relatively large number of healthy subjects (more than 10) exists in the literature(Nils Daniel Forkert et al, 2012), making ours the first publicly available.…”
supporting
confidence: 91%
“…Notably, this relationship was also observed in arteries(Figure 3, R = [.46, .52], all p < .001).Moreover, to the best of our knowledge, no group-based probabilistic venous atlas with a relatively large number of healthy subjects (more than 10) exists in the literature(Nils Daniel Forkert et al, 2012), making ours the first publicly available. Our segmentation results are similar to the probabilistic map of vasculature based on 10 subjects(Ward et al, 2018) and a deterministic map of large vein atlases,…”
supporting
confidence: 69%
See 2 more Smart Citations
“…MRI is a noninvasive technique that provides excellent soft tissue contrast, and the relatively recent development of susceptibility‐weighted imaging (SWI) has dramatically improved the visibility of small veins . A number of algorithms making use of Hessian filters have been proposed to facilitate the segmentation of blood vessels made visible by SWI . In this work, we build on the Steger algorithm to create a Hessian‐based segmentation technique, which takes advantage of the increased signal and contrast available at MRI strengths of 7 T to detect venous structures in vivo.…”
Section: Introductionmentioning
confidence: 99%